Influence of Customer Experience Management Analysis in Increasing Customer Loyalty of PT Bank Jago Tbk in Indonesia - Fahri Muhammad Fasya; Tarandhika Tantra (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The primary objective of this research paper is to comprehensively examine and evaluate the impact of customer experience management, particularly virtual interaction, physical interaction, and service interaction, on customer loyalty within PT Bank Jago Tbk, a prominent financial institution in Indonesia. Employing an explanatory research design, the study collected data from a carefully selected sample of 200 respondents. To establish the significance of the proposed study model, a comprehensive multiple regression analysis was conducted. The research findings substantiate a positive and meaningful relationship between customer experience management and customer loyalty. Furthermore, the dimensions of customer experience management, including physical interaction, virtual interaction, and service interaction, were determined to be statistically significant in explaining customer loyalty behavior. The study holds valuable practical implications for Bank Jago as it seeks to establish and maintain a competitive advantage in the ever-evolving digital business landscape. Consequently, the research paper presents an enhanced model of customer experience management that directly correlates with consumer loyalty, providing valuable insights for both academia and industry practitioners.